Qualitative and quantitative aspects of climate change in Ghardaia (Algeria) - ANSAR , Allaoua; AZAIEZ , Naima (Journal of Human Sciences, 2020)
Climate change is a hot topic. All the research covering this subject confirms its veracity. Since the end of the 20th century,  the Earth has been facing a climatic evolution that often results in a thermal rise and a regression of the rains, with clear trend to drought. In this research, we try, through the climatic data of the Ghardaïa station (Algeria), to confirm or remove this truth through a comparative statistical approach. To achieve this purpose, we compare the thermal and rainfall data for the period 1986 -2017 with  those  for the period 1913-38 at the three time scales (monthly, seasonal and annual). In this article, we will focus on three themes of great importance, the qualitative climatic evolution through the rise and fall for both parameters, the quantitative aspect of this evolution.  Establish climate synthesis  in order to determine the tendency to drought and / or humidity.